Perspective: Vitamin D deficiency and COVID-19 severity - plausibly linked by latitude, ethnicity, impacts on cytokines, ACE2 and thrombosis. - Kenny, Rose (My University, 2020)
SARS‐CoV‐2 coronavirus infection ranges from asymptomatic through to fatal COVID‐19 characterized by a ‘cytokine storm’ and lung failure. Vitamin D deficiency has been postulated as a determinant of severity.
PUBLISHED
Keywords: SARS‐CoV‐2 coronavirus; ‘cytokine storm’; Vitamin D deficiency; SARS‐CoV‐2 coronavirus; ‘cytokine storm’; Vitamin D deficiency; Ageing